2019
DOI: 10.1186/s12884-019-2466-5
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Accreta Spectrum (PAS) disorders: incidence, risk factors and outcomes of different management strategies in a tertiary referral hospital in Minia, Egypt: a prospective study

Abstract: Background Placenta accreta spectrum (PAS) disorders have become a significant life-threatening issue due to its increased incidence, morbidity and mortality. Several studies have tried to identify the risk factors for PAS disorders. The ideal management for PAS disorders is a matter of debate. The study objectives were to evaluate the incidence and risk factors of PAS disorders and to compare different management strategies at a tertiary referral hospital, Minia, Egypt. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 49 publications
13
49
1
2
Order By: Relevance
“…As a result, more placental implantation pathologies occur [26], and certainly more problems related to scar dehiscence following repeated pregnancies following Cesarean Sections.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, more placental implantation pathologies occur [26], and certainly more problems related to scar dehiscence following repeated pregnancies following Cesarean Sections.…”
Section: Discussionmentioning
confidence: 99%
“…Cervix as natural tamponade (by inverting the anterior or posterior lip of the cervix and suturing with the placental bed in the anterior or posterior wall of the uterus) was also reported from Egypt as safe, simple, time-saving and effective method for controlling PPH caused by placenta previa or placenta previa accreta (48). The same authors reported cervical tamponade with bilateral uterine artery ligation and removal of the placenta after a month on elective base as a safe alternative method to hysterectomy in those women who wish to preserve their fertility (49). In general, the devascularization procedures in option IV are not limited to the bilateral anterior division of internal iliac artery ligations like Shabana and colleagues 'stepwise approach', it entertains multiple alternative modalities.…”
Section: Option IV (Expectant Management With Conservative Interventimentioning
confidence: 90%
“…Large case series studies (which had included >30 cases of expectant management) are summarized in Table 1 (18,20,40,42,44,49,62,60,61,63,64) to show the outcomes of uterine preserving interventions. As there were plenty of success stories in non-percreta cases, in terms of avoiding hysterectomy, there were also failures, primarily due to serious complications requiring immediate and delayed hysterectomy.…”
Section: Commentmentioning
confidence: 99%
“…The prevalence of PAS has increased about eight times since 1970s ( Silver and Branch, 2018 ). A study showed that the overall proportion of PAS in recent years had even reached 0.91% ( El Gelany et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%